An Analysis of the Concepts of Conflict and Conflict Resolution in Malay - Asmah Haji Omar (Journal of Modern Languages)
This study makes use of the field theory, viz, a theory that treats a related set of words belonging to a domain (Adrienne Lehrer, 1974:3). The domains that are of interest here are the domains of conflict and conflict resolution. In analysing the terms for conflict and conflict resolution, the focus of the study is on the distinguishers more than the shared primitives. The paper mentions that the recognition of the distinguishers enables us to divide each field accordingly into subfields.